Formation of Cognitive Interests in Primary School Children - Majidovna, Muhammadiyeva Matlyuba (European Journal of Life Safety and Stability (2660-9630), 2023)
The article reveals the problem of forming the cognitive interests of primary school students through project activities. Design, as a form of learning activity, is an effective way to develop knowledge, skills, personal achievements, individual vision in solving learning problems. Project activity in primary school is always a joint activity that develops the cognitive interests of primary school students, aimed at creativity and achieving a specific result.